2016
DOI: 10.1007/s00382-016-3001-2
|View full text |Cite
|
Sign up to set email alerts
|

Sea-level variability in the Mediterranean Sea from altimetry and tide gauges

Abstract: mean sea-level and the coastal stations. From 1993 to 2012, the mean sea-level trend (2.44 ± 0.5 mm year −1 ) was found to be affected by the positive anomalies of 2010 and 2011, which were observed in all the cases analysed and were mainly distributed in the eastern part of the basin. Ensemble empirical mode decomposition showed that these events were related to the processes that have dominant periodicities of ∼10 years, and positive residual sea-level trend were generally observed in both data-sets. In term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 74 publications
14
50
0
2
Order By: Relevance
“…In the Mediterranean Sea, the sea level trend estimation (2.8 ± 0.26 mm year −1 ) was consistent with the results of previous studies based on in-situ and remote-sensing observations [34,101] when the resultant of the mass and thermosteric components was considered. This was not the case when the halosteric component was included, whose trends have high negative values that can lead to discrepancies when compared with the sea level trends obtained from observations (e.g., remote sensing), as underlined by Legeais et al [34].…”
Section: Regionsupporting
confidence: 90%
“…In the Mediterranean Sea, the sea level trend estimation (2.8 ± 0.26 mm year −1 ) was consistent with the results of previous studies based on in-situ and remote-sensing observations [34,101] when the resultant of the mass and thermosteric components was considered. This was not the case when the halosteric component was included, whose trends have high negative values that can lead to discrepancies when compared with the sea level trends obtained from observations (e.g., remote sensing), as underlined by Legeais et al [34].…”
Section: Regionsupporting
confidence: 90%
“…of a few fractions of mm yr −1 Galassi and Spada, 2014b;Bonaduce et al, 2016). Future rates of GIA-induced sea-level variations across the whole Mediterranean Sea (Galassi and Spada, 2014a) will not change with respect to current trends since this phenomenon only evolves on millennial timescales.…”
Section: Sea-level Variabilitymentioning
confidence: 98%
“…In terms of the basic/core products that can be derived from observations, we have reported some of the gaps in coverage in both space and time for the different platforms, which are mainly due to the lack of observing planning at the Mediterranean Sea basin scale. Bonaduce et al (2016) demonstrated that the absence of sea level stations along the southern coasts means that estimating the basin mean sea level trend is not possible simply from tide gauges.…”
Section: Gapsmentioning
confidence: 99%